(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article studies epistemological changes in these fields influenced the reading of the Bible and did not cease doing so. Here we will analyzed clear defenders of Copernicans recognized that the Bible consists of historical texts. And stresses the Bible was written in a language attuned to people at a certain time and place in history. Here mentioned about the information accommodator highlighted the historicity of the Bible.